Trichomonas vaginalis Weakens Human Amniochorion in an In Vitro Model of Premature Membrane Rupture - Deborah Draper; Ward Jones; R. Phillip Heine; Michelle Beutz; Janice I. French; James A. McGregor (Hindawi Limited, 1995)
Objective: Trichomonas vaginalis (TV) infection is associated with preterm rupture of membranes (PROM) and preterm birth. We evaluated the effects of TV growth and metabolism on preparations of human amniochorion to understand and characterize how TV may impair fetal-membrane integrity and predispose to PROM and preterm birth.